Biometric parameters and structure of millet yield depending on growing conditions - Kostenko, M. (Scientific Progress & Innovations, 2023)
The article analyzes the biometric parameters and yield structure of millet varieties depending on growing conditions. The aim of the study is to determine the influence of growing conditions on biometric parameters and structure of millet yield. The forest-steppe zone is characterized by the most optimal conditions for growing stubble millet. Due to climate change, the number of warm days is increasing, so the cultivation of pearl millet and stubble crops is becoming increasingly important. Sowing of millet was carried out by the usual row and wide-row method with seeding rates ‒ 22 and 18 kg/ha. Millet was sown after the following predecessors: black fallow, perennial grasses, peas and winter wheat. The following varieties of ultra-early maturing millet were grown: Bila Altanka, Cinderella and Poltavske Zolotyste. The article analyzed the weather conditions during the experiment, phenological observations, average height of millet and the structure of the millet crop. The hottest month was August. After sowing millet, the greatest amount of precipitation was observed, especially in the first decade of August. Shoots appeared in all plants at the same time. The plants sown after peas were the first to ripen, and the latest after winter wheat. The largest number of inflorescences was formed in plants sown after peas, but a large number of them are unproductive. Therefore, the variety Poltavske zolotyste sown in a row method has the largest number of inflorescences ‒ 358 pcs./m2 of which 185 are productive. In this variant, only half of the inflorescences will yield a crop. Variety Bila Altynka sown in a row method after perennial grasses has absolutely all productive inflorescences. The tallest plants were after peas. The variety Bila Altynka sown in wide-row method had the highest height at the time of harvesting ‒ 109 cm. The lowest plants were after winter wheat in crops with a row method of sowing. In particular, the minimum height at the time of harvesting was in the variety Poltavske Zolotyste ‒ 42 cm. The best indicators of the structure of the millet harvest has the variety Bila Altanka sown in pairs by wide-row method: weight of 1000 seeds ‒ 8.1 g, panicle length ‒ 22 cm, number of seeds per panicle ‒ 346 pcs. and the weight of grain per inflorescence ‒ 2.8 g.